The Routledge Handbook of Ecomedia Studies (Routledge Environment and Sustainability Handbooks, 2023)
The Routledge Handbook of Ecomedia Studies gathers leading work by critical scholars in this burgeoning field. Redressing the lack of environmental perspectives in the study of media, ecomedia studies asserts that media are in and about the environment, and environments are socially and materially mediated. The book gives form to this new area of study and brings together diverse scholarly contributions to explore and give definition to the field. The Handbook highlights five critical areas of ecomedia scholarship: ecomedia theory, ecomateriality, political ecology, ecocultures, and eco-affects. Within these areas, authors navigate a range of different topics including infrastructures, supply and manufacturing chains, energy, e-waste, labor, ecofeminism, African and Indigenous ecomedia, environmental justice, environmental media governance, ecopolitical satire, and digital ecologies. The result is a holistic volume that provides an in-depth and comprehensive overview of the current state of the field, as well as future developments. This volume will be an essential resource for students, educators, and scholars of media studies, cultural studies, film, environmental communication, political ecology, science and technology studies, and the environmental humanities. The Open Access version of this book, available at www.taylorfrancis. com, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives (CC-BY-NC-ND) 4.0 license. Deep gratitude for the generous support of those institutions that provided funding to enable this volume to be available simultaneously in print and open access: University of Oregon Libraries Open Access Publishing Award, Frank J. Guarini School of Busi-ness at John Cabot University, University of Vermont Humanities Center, University of California Santa Barbara, University of Lausanne, and School of Humanities at Nanyang Technological University.